Exploring the potential impact of herbal antioxidants on human cardiovascular diseases (Sciences of Phytochemistry, 2023)
The body's antioxidant system efficiently neutralizes reactive oxygen species, which are intermediates formed during routine metabolic activity. Oxidative stress resulting from an imbalance in this neutralization process is known to be a key factor in many human ailments, including atherosclerosis and various cardiovascular diseases. Observational epidemiological research conducted over the past several decades has shown that consumption of vegetables and fruits rich in vitamins and antioxidants is associated with a reduced incidence of cardiovascular disease. However, it is crucial to exercise caution when considering the use of herbal antioxidants as a treatment for various ailments, including cardiovascular conditions. This caution arises from concerns related to their safety, potentially life-threatening side effects, toxicity, and potential interactions with other medications. Multiple research studies have highlighted these risks associated with antioxidant usage as a form of medical intervention. This overview briefly summarizes cardiovascular disease, associated risk factors, and the role of reactive oxygen species and oxidative stress in its development. Next, delve into some of the most significant plant-based antioxidants, their therapeutic uses, as well as the potential benefits and drawbacks of using them to treat various diseases, with a particular focus on their relevance to cardiovascular disease.